The relationship between habit and healthcare professional behaviour in clinical practice: a systematic review and meta-analysis. Issue 1 (2nd January 2019) - Potthoff, Sebastian; Rasul, Othman; Sniehotta, Falko F.; Marques, Marta; Beyer, Fiona; Thomson, Richard; Avery, Leah; Presseau, Justin
ABSTRACT: Theories of behaviour used to understand healthcare professional behaviour often focus on the deliberative processes that drive their behaviour; however, less is known about the role that implicit processes such as habit have on healthcare professional behaviour. This systematic review aimed to critically appraise and synthesise research evidence investigating the association between habit and healthcare professional behaviour. A search of five databases (PsycINFO, EMBASE, Scopus and CINAHL) was conducted up until 29 February 2016 to identify studies reporting correlations between habit and healthcare professional behaviours. Meta-analyses were conducted to assess the overall habit-behaviour association across all behaviours. A subgroup analysis assessed whether the habit-behaviour relationship differed depending on whether the behaviour was objectively measured or assessed by self-report. We identified nine eligible studies involving 1975 healthcare professionals that included 28 habit-behaviour correlations. A combined mean r + of 0.35 (medium effect) was observed between habit and healthcare professional behaviour. The habit-behaviour correlation was not affected by whether behaviour was measured objectively or by self-report. This review suggests that habit plays a significant role in healthcare professional behaviour. Findings may have implications for considering health professionals' habit when promoting the provision of evidence-based health care, and for breaking existing habit when de-implementing outdated, non-evidence-based practices.